Line mixing and broadening in the v(1→3) first overtone bandhead of carbon monoxide at high temperatures and high pressures. (December 2019) - Bendana, Fabio A.; Lee, Daniel D.; Wei, Chuyu; Pineda, Daniel I.; Spearrin, R. Mitchell
Highlights: Broadening parameters measured for high rotational energy lines ( J ″ = 42-58) of CO. Collisional line mixing modeled using an empirical modified exponential gap law. Thermodynamic scaling of collisional effects examined up to 3750 K and 60 atm. Abstract: Temperature-dependent line mixing and line broadening parameters were empirically-determined for 17 rovibrational transitions in the v (1→3) bandhead of carbon monoxide near 2.3 µm. Collisional effects on the high rotational energy lines ( E ″ = 5500–8600 cm − 1 ) in the R-branch were studied over a range of temperatures from 1200–3750 K in a shock tube and heated gas cell. Measured spectra comprising the target lines in Ar and CO bath gases were fit with Voigt profiles at near-atmospheric pressures to determine line-broadening coefficients, with temperature dependence accounted by a power law. With line broadening established, line-mixing effects were examined at elevated pressures up to 60 atm at similar temperatures, reflecting conditions in high-pressure combustion environments. A modified exponential gap model for line mixing was developed to capture the pressure and temperature dependence of collisional transfer rates for the bandhead region using the relaxation matrix formalism.